Financial Knowledge Performance Owners MSMEs Terhadap Penggunaan Informasi Akuntansi - Yayuk Marliza; Miki Indika; Rian Okta Vianie (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine whether level of education MSMEs Owners have an effect the use of accounting information in subdistrict eastern Lubuklinggau, Lubuklinggau city. This research uses a Simple Random Sampling technique and data collection using a questionnaire distributed to respondents, namely MSMEs owners. The data analysis technique uses multiple linear regression. The results showed that level of education have a significant influence on used for accounting information. This shows that the owner's understanding of the use of information will be an obstacle if it is not sharpened through good education, because they do not yet know the importance of using accounting information for their business if the education they have is still low